2020
DOI: 10.1002/agg2.20062
|View full text |Cite|
|
Sign up to set email alerts
|

Yield and quality of three potato cultivars under series of nitrogen rates

Abstract: Undesirable growth of potato (Solanum tuberosum L.) crop under an excessive N fertilizer application is the main obstacle presently. This research was conducted to investigate the response of different potato cultivars; Russet Burbank, Shepody, and Superior, and its qualitative characteristics under a series of N rates. Six rates of N fertilization (0–280 kg ha−1) were applied on 11 sites in a randomized complete block design, with four replications. Sites with ≥30 g kg−1 of soil organic matter (OM) produced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…Although only one potato variety, Russet Burbank, which is the predominant processing variety grown commercially in the northeast, was used in this study, observed results should be generally applicable to other potato varieties as well. Previous studies in this region have indicated similar responses to rotations, amendments, and fertilization in multiple different potato varieties [29][30][31][32]36], and improvements in soil health have been associated with increases in yield across not only different potato varieties but many different crops as well [4,6,[12][13][14][15]44].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Although only one potato variety, Russet Burbank, which is the predominant processing variety grown commercially in the northeast, was used in this study, observed results should be generally applicable to other potato varieties as well. Previous studies in this region have indicated similar responses to rotations, amendments, and fertilization in multiple different potato varieties [29][30][31][32]36], and improvements in soil health have been associated with increases in yield across not only different potato varieties but many different crops as well [4,6,[12][13][14][15]44].…”
Section: Discussionmentioning
confidence: 86%
“…However, based on the results observed and the characteristics of these systems, it is apparent that improvements in properties associated with the ability to store and hold soil water were at least partially, if not primarily, responsible for the yield increases observed in the SI system, rather than such aspects as nutritional improvements. First, all systems were supplied with adequate (above optimal NPK) fertilization so as not to limit productivity based on numerous studies in this area [29][30][31][32][33]. Additional NPK fertility above these levels provided by the compost amendments would not be expected to increase yield further, as studies have indicated depressed yields, not increased yields, with above optimal fertilizer additions [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selected VIs were calculated based on the multispectral UAV images (Table 2). These VIs were normalized using GDD (N VI ), which is particularly useful when combining data from different site-years and growth stages [10,34]. The N VI was computed by dividing the VI data by the accumulated GDD from planting to sensing, as shown in Equation (3).…”
Section: Discussionmentioning
confidence: 99%